Cis‐regulatory control of Mesp1 expression by YY1 and SP1 during mouse embryogenesis. Issue 3 (3rd November 2015) - Beketaev, Ilimbek; Zhang, Yi; Weng, Kuo‐Chan; Rhee, Siyeon; Yu, Wei; Liu, Yu; Mager, Jesse; Wang, Jun
Abstract : Background: Mesp1 is critical for early cardiomyocyte differentiation and heart development. We previously observed down‐regulation of Mesp1 expression in YY1‐ablated mouse embryonic hearts. However, how Mesp1 expression is mediated by YY1 is not well understood.Results: We excised YY1 in the murine embryos using Sox2‐cre and found that Mesp1 was down‐regulated in the embryonic day (E) 7.5 mutant embryos. Also, YY1 activated the 6 kb Mesp1 regulatory element fused to a luciferase reporter. We identified two putative YY1 binding sites in the proximal promoter region of Mesp1 gene, and found that mutation of these sites significantly reduced YY1‐induced activation of the Mesp1 promoter. We also uncovered one cognitive site for SP1, one of the earliest binding partners of YY1 identified. Mutation of this SP1 site repressed SP1‐induced activation of the Mesp1 promoter. Moreover, YY1 and SP1 synergistically activated the Mesp1 promoter. Consistently, while Lacz expression driven by the wild‐type 6 kb regulatory element of Mesp1 gene was robust in E7.5 mouse embryos, the mutation of these binding sites in the context of this 6 kb sequence substantially reduced the LacZ expression during embryogenesis.Conclusions: YY1 and SP1 independently and cooperatively govern the Mesp1 expression during embryogenesis. Developmental Dynamics 245:379–387, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Ablation of YY1 by Sox1‐cre+ results in decrease in Mesp1 expression in the mutant embryos. YY1 dosed‐dependently activates the regulatory element of Mesp1 gene. Mutation of either of the two putative YY1 binding sites in the Mesp1 proximal promoter reduces reporter activation by YY1 and LacZ expression. Mutation of the proximal SP1 binding site in the Mesp1 promoter reduces reporter activation by SP1 and LacZ expression. Endogenous YY1 and SP1 occupy respective cognitive sites in the proximal promoter of Mesp1 gene, and are involved in mediating Mesp1 expression during embryogenesis.